Environmental compensation to recover damages to permanent preserved areas caused by the occupation of continental fish farms: a case study in Santa Catarina, Brazil - Bruna Roque Loureiro; Michele Monguilhott; Eric Arthur Bastos Routledge; Fabiano Müller Silva; Alex Pires de Oliveira Nuñer (Ciência Rural)
ABSTRACT: The environmental regulation of continental fish farming in Brazil is closely linked to land occupation and use. Areas used for this activity are mostly located in permanent preservation areas (PPA), close to rivers and springs, demonstrating the necessity of regulating this activity for its compliance with public policy. Santa Catarina is a leading state in fish farming and one of the first to regulate the use of PPAs. The feasibility of a proposal for environmental compensation to regularize the use of PPAs in Santa Catarina for fish farming; was therefore, assessed. The results showed that 74% of the fish farms analyzed need to regularize the occupation of production structures in PPAs. Regarding the proposed index of compensation for use in PPAs, the environmental compensation factor (ECF), through evaluation of the individual maps and subsequent integrated evaluation, all the fish farms identified with environmental liabilities in occupation had ratios of 1:2 and 1:3, and this index is a viable alternative for environmental regularization of the activity. It was further proposed that ECF be applied to small fish farms of up to four fiscal modules and that they have a standard minimum occupancy profile in relation to the total area of the property, as assessed in the present study.